Endophytic Microbiota Comparison of Dendrobium huoshanense Root and Stem in Different Growth Years - Chen, Shaotong; Dai, Jun; Song, Xiangwen; Jiang, Xueping; Zhao, Qun; Sun, Chuanbo; Chen, Cunwu; Chen, Naifu; Han, Bangxing (Planta Medica, 2019)
The endophytic microbiome in medicinal plants is rich and diverse, but few studies have followed the endophytic microbiome of medicinal plants in different tissues with their growth. In this study, we examined the endophytic bacterial and fungal community structures associated with both the stem and root compartments of Dendrobium huoshanense at different growth years via high-throughput sequencing of 16S rRNA genes and nrDNA fragments of internal transcribed spacer regions. Results indicated that more diverse prokaryotic and fungal operational taxonomic units were detected in roots than in stems, and the alpha diversity of endophytic prokaryotic significantly differed among the 1-, 2-, and 3-year-old roots. The dominant bacterial phyla Proteobacteria Firmicutes, Actinobacteria, Bacteroidetes, and Acidobacteria, and fungal phyla Ascomycota, Basidiomycota, and Ascomycota were detected in the stems and roots with 3 growth years. Moreover, linear discriminant effect size analysis revealed 138 differentially abundant taxonomic clades in the bacterial level, and 197 in the fungal level in six groups. Our results provide evidence for endophytic microbiota communities depending on the tissues and growth years of D. huoshanense. The results from this study should be useful to better understand medicinal plant-microbe interactions.
Keywords: Dendrobium huoshanense; endophytic microbiota; overlap; growth years